Biocontrol potential of Arabidopsis thaliana against Biomphalaria glabrata, the intermediate host of Schistosoma mansoni, focusing on biological, physiological, histopathological, and genotoxic impacts - Najla Y. Beit Elmal; Fathy A. Abdel Ghaffar; Salwa A.H. Hamdi; Amina M. Ibrahim; Mona F. Fol; Nesma A. Mostafa (Parasite Epidemiology and Control)
Controlling Biomphalaria species with plant products is crucial in the treatment of schistosomiasis since it is eco-friendly and generally less harmful to non-target organisms. The goal of this study was to determine the molluscicidal activity of an aqueous extract of Arabidopsis thaliana leaves against Biomphalaria glabrata. A preliminary phytochemical screening test revealed the presence of flavonoids, terpenoids, steroids, anthraquinones, alkaloids, saponins, tannins, and carbohydrates. Following exposure to sub-lethal concentrations (LC10 75.62 mg/L and LC25 90.52 mg/L) of aqueous extract of A. thaliana, a reduction in survival, reproductive, and fecundity rates of B. glabrata were detected, as well as a substantial decrease in GSH, CAT, and SOD, while increasing MDA and NO levels. In addition, there was an increase in liver and renal functions as well as lipid profiles, compared to the control group. Histopathological examination of the digestive gland of treated B. glabrata showed a shrinkage of the tubules and an increase in the inter-tubular spaces as well as degeneration in the oocytes and spermatocytes of the hermaphrodite glands with a loss of connective tissues between the acini. Also, the comet assay revealed a genotoxic effect of aqueous extract of A. thaliana on B. glabrata, with a significant increase in the tail moment, tail length, and DNA percentage reflecting DNA damage compared to the control group. Conclusively, Arabidopsis thaliana aqueous extract acts as a natural molluscicidal agent against Biomphalaria glabrata.